1987
DOI: 10.1111/j.1365-2672.1987.tb02690.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Erwinia carotovora in surface water in North America

Abstract: Erwinia carotovora was frequently isolated from samples of surface water collected from 66 rivers, springs, creeks, streams, lakes, reservoirs and ponds in 16 states in the US but was not found in the single fresh water sample collected in Canada. The organism was also isolated from water collected from the Pacific Ocean and the Gulf of Mexico. In Colorado and Wyoming, E. carotovora was isolated from water samples nearly every month of the year when monthly samples were collected from several streams. Erwinia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Dickeya chrysanthemi (formerly Erwinia chrysanthemi) is thought to be a part of the indigenous microorganisms on weeds and in sediments in alpine streams in Australia (Cother and Gilbert, 1990). Numerous studies illustrated that Pectobacterium carotovorum (formerly E. carotovora) is present in a wide range of surface and underground waters including those used in irrigation (McCarter-Zorner et al, 1984;Harrison et al, 1987). Franc (1988) further revealed that this bacterium was present in at least 80% of samples of ocean water and rainwater collected on the west coast of the United States and in samples of aerosols along the coast.…”
Section: Discussionmentioning
confidence: 99%
“…Dickeya chrysanthemi (formerly Erwinia chrysanthemi) is thought to be a part of the indigenous microorganisms on weeds and in sediments in alpine streams in Australia (Cother and Gilbert, 1990). Numerous studies illustrated that Pectobacterium carotovorum (formerly E. carotovora) is present in a wide range of surface and underground waters including those used in irrigation (McCarter-Zorner et al, 1984;Harrison et al, 1987). Franc (1988) further revealed that this bacterium was present in at least 80% of samples of ocean water and rainwater collected on the west coast of the United States and in samples of aerosols along the coast.…”
Section: Discussionmentioning
confidence: 99%
“…It is a ubiquitous pathogen that survives in soil, surface and ground water, and it has been associated with a variety of invertebrates [1], [2], [3], [4]. P. carotovorum attacks plant tissue by secreting an array of plant cell wall degrading enzymes through the type II secretion system [5], [6], [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both pathogens can easily be detected in diseased plant tissue. They can also be found as contaminants of healthy-looking plants and tubers as well as free-living in surface waters (Harrison et al, 1987;Pkrombelon & Hyman, 1987;Persson & Hegart, 1990). E.c.…”
Section: Introductionmentioning
confidence: 99%